2014
DOI: 10.1136/vr.101574
|View full text |Cite
|
Sign up to set email alerts
|

Mesna and furosemide for prevention of cyclophosphamide‐induced sterile haemorrhagic cystitis in dogs – a retrospective study

Abstract: Sterile haemorrhagic cystitis (SHC) is a possible side effect of cyclophosphamide which can severely impact quality of life. Mesna and diuresis are effective in human medicine to prevent SHC. The aim of the present study was to compare the efficacy of mesna versus diuresis with furosemide in preventing SHC in dogs treated with cyclophosphamide within a multidrug chemotherapy induction protocol for malignant lymphoma. Medical records of dogs treated at the Clinic of Small Animal Medicine, Munich, between 1997 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…The overall incidence of SHC in the University of Wisconsin-Madison dogs enrolled in this study was 8.9%. This is comparable to other studies, in which SHC was found in 3.8% to 9.0% of pulsetreated dogs, 15,21,25,26 and in 3.6% to 32% of metronomic CP-treated dogs 13,16,18,27 Metronomic CP was a significant risk factor for SHC in our study. Cumulative CP doses were nearly 3-fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The overall incidence of SHC in the University of Wisconsin-Madison dogs enrolled in this study was 8.9%. This is comparable to other studies, in which SHC was found in 3.8% to 9.0% of pulsetreated dogs, 15,21,25,26 and in 3.6% to 32% of metronomic CP-treated dogs 13,16,18,27 Metronomic CP was a significant risk factor for SHC in our study. Cumulative CP doses were nearly 3-fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC.…”
Section: Discussionsupporting
confidence: 91%
“…Cumulative CP doses were nearly 3‐fold higher with metronomic compared to pulse protocols, and higher cumulative doses are a risk factor for SHC . The metronomic CP protocol in our population did not include furosemide, which may have increased SHC risk . However, SHC can develop after even a single dose of intravenous CP or in the presence of furosemide, so other factors are likely involved.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The paper by Laberke and others (2014), summarised on p 250 of this issue of Veterinary Record , should be of interest to those in small animal practice, in highlighting the risk of haemorrhagic cystitis in dogs receiving cyclophosphamide and in demonstrating the efficacy of medical prophylaxis of this serious adverse effect when high-dose cyclophosphamide protocols (for example, CHOP) are used. It shows that in this group of dogs, furosemide diuresis was as effective as the more expensive and complicated mesna option.…”
mentioning
confidence: 99%